2015
DOI: 10.1261/rna.052712.115
|View full text |Cite
|
Sign up to set email alerts
|

A glyS T-box riboswitch with species-specific structural features responding to both proteinogenic and nonproteinogenic tRNAGly isoacceptors

Abstract: In Staphylococcus aureus, a T-box riboswitch exists upstream of the glyS gene to regulate transcription of the sole glycyl-tRNA synthetase, which aminoacylates five tRNA Gly isoacceptors bearing GCC or UCC anticodons. Subsequently, the glycylated tRNAs serve as substrates for decoding glycine codons during translation, and also as glycine donors for exoribosomal synthesis of pentaglycine peptides during cell wall formation. Probing of the predicted T-box structure revealed a long stem I, lacking features previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 63 publications
(124 reference statements)
0
34
0
Order By: Relevance
“…Notably, while most translational T-boxes lack the long Stem I's, they frequently sport additional insertions in their discriminator domains, such as in Stem III and especially in Helix A2 (i.e., on top of the antiterminator). These features may aid the folding of the discriminator helical elements and facilitate their refolding between the conformers, or even make additional contacts to the tRNA acceptor stem, as proposed for the Stem Sa in the Staphylococci glyQ Tboxes (Apostolidi et al, 2015;Stamatopoulou et al, 2017).…”
Section: Differences In Sequence and Structurementioning
confidence: 99%
“…Notably, while most translational T-boxes lack the long Stem I's, they frequently sport additional insertions in their discriminator domains, such as in Stem III and especially in Helix A2 (i.e., on top of the antiterminator). These features may aid the folding of the discriminator helical elements and facilitate their refolding between the conformers, or even make additional contacts to the tRNA acceptor stem, as proposed for the Stem Sa in the Staphylococci glyQ Tboxes (Apostolidi et al, 2015;Stamatopoulou et al, 2017).…”
Section: Differences In Sequence and Structurementioning
confidence: 99%
“…To address this hypothesis, we cloned the unlinked genes encoding thioredoxin (trxA) or thioredoxin reductase (trxB) on multicopy plasmids and placed the genes under the control of the T box riboswitch of the glycyl-tRNA synthetase gene promoter PglyS (SAOUHSC_01666) (44,46). This promoter is not known to be regulated by Spx and would be expected to exert housekeeping levels of gene expression, since S. aureus encodes only one glycyl-tRNA synthetase.…”
Section: Figmentioning
confidence: 99%
“…Recent studies focused on the characterization of T-boxes from pathogenic bacteria revealed unexpected complexities of T-box systems both at the structural and biochemical level. T-boxes are no longer considered of single tRNA specificity and can contain species-specific structural features, like SL with tandem or overlapping codons ( 22 , 23 ). Certain T-boxes, exemplified by those in Actinobacteria, control translation initiation instead of transcription, in comparable genomic contexts ( 24 ).…”
Section: Introductionmentioning
confidence: 99%